Teaching performance in the academic performance of students of the UNMSM professional school of tourism administration in virtuality - Loyola Santos, Johanna Del Carmen (2024)
This scientific study is carried out with the purpose of analyzing whether there is a relationship between teaching performance and the academic performance of the student at the FCA-UNMSM School of Tourism Administration. A non-experimental design with a quantitative approach was used. 100 students with active enrollment in the fourth cycle participated, to whom a survey was applied to measure the teaching performance variable and a checklist to collect information on final averages. After descriptive and inferential statistical analysis, we concluded the existence of a direct and positive relationship between teaching performance and academic performance. These instruments were duly validated through expert judgment and their reliability was determined using Cronbach's Alpha test. To contrast hypotheses, Spearman's correlation coefficient was used. The result indicates that there is a direct, positive, high (rho: 0.716) and significant (Sig. =0.000, p<0.05) relationship between the two study variables.